ANALISA SIFAT KETEGUHAN PATAH DAN TEKAN BETON SEMEN DARI TULANG ROTAN - Purwanto, Djoko (Jurnal Riset Industri Hasil Hutan, 2014)
Indonesia has the potential of rattan is  enough large, but the value of the sale and utilization is still limited as materials for baskets, furniture,  handicrafts and so on. This research purpose to obtain bending and compressure strength properties when the rattan used for substitution  of iron materaial making to  cement concrete building simple houses. The raw material of used for research this is rattan has done processing (preservation and drying). Cement concrete frame made of rattan and molds for casting. Concrete frame rattan incorporated in the mold and filled dough (cement: gravel: sand = 1: 2: 3 plus water as needed). Treatment was observed that the diameter rattan (A) which includes: 8 mm (a1), 10 mm (a2) and 12 mm (a3); and the distance between the iron ring (B) which includes 11 cm (b1); 15 cm (b2); and 19 cm (b3). The number of repeat 3 times. Parameters observed bending and compressure strength.The results of the research rattan diameter 8-12 mm and the distance ring iron 11-19 cm produces bending strength from 18.24 to 40.13 kg /cm2 lower than cement concrete from iron materials (95.76 to 120.36 kg / cm2); and compressure strength from 28.33 to 42.85 kg/cm2 larger                                         than from iron cement concrete materials (20 to 34.67kg/cm2). The results of the research show  bending strength from rattan lower and compressure sterngth than big concrete from iron.Keywords: rattan, cement concrete, bending strength, compressure strength